Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21037/mhealth.2019.12.08
|View full text |Cite
|
Sign up to set email alerts
|

The mHealth in the canine assisted therapy: the design and application of a kit for the wearable monitoring during a walking session

Abstract: Background: We are today assisting to an increasing interest to the animal assisted therapy (AAT). Among the goals of the AAT there is to improve a patient's psychological and physiological condition during the rehabilitation therapies. Several studies showed the health benefits (psychological and physiological) for the human subject thanks to the AAT. Today, according to the new central position of the pet, the approach must be revised in a more general and bidirectional approach embedding the assessment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Several studies have shown that pets are valid support during strong emotional stress [23][24][25][26]. However, it has been reported the importance of objectively quantifying such a positive pet-owner interaction [16,17] to overcome emotional distress [27]. The eS developed and presented herein has been promptly submitted through modern communication Apps, to 4993 subjects, receiving almost all responses within 6 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that pets are valid support during strong emotional stress [23][24][25][26]. However, it has been reported the importance of objectively quantifying such a positive pet-owner interaction [16,17] to overcome emotional distress [27]. The eS developed and presented herein has been promptly submitted through modern communication Apps, to 4993 subjects, receiving almost all responses within 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism which explains the positive effect of the owner-pet interaction is currently under study; however, some studies suggested that these positive effects can depend on (a) the encouragement to do physical activity while walking the dog and (b) the co-presence of a pet [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have highlighted the need to quantify this mitigating effect through specific procedures, complaining that the positive impact of companion animals is difficult to calculate, even if it is a simple co-presence [ 25 , 26 ]. Another study highlighted a new way of applying the AAT [ 27 ]. We are today, in fact, assisting to an increasing interest in both animal-assisted therapy (AAT) and the pet quality of life and health.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in the pet quality of life and health is a direct consequence of the recognition of its contribution to the society. Today, according to the new central position of the pet, the approach must be revised in a more general and bidirectional approach embedding the assessment of the health benefits contemporary for the two actors, human and pet [ 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%